Electrophoretic separation of tissue-specific serum alkaline phosphatases - Canapa-Anson, R. (1970)
Previous electrophoretic methods for the separation of tissue-specific serum alkaline phosphatases have either been unable to separate the liver and bone enzymes or have been too involved for routine clinical use. A relatively simple electrophoretic method is described which separates placental, liver, bone, and intestinal alkaline phosphatases in serum. The clinical applications of such a method appear to be mainly in the differential diagnosis of liver and bone disease, especially in complicated hypercalcaemic states where tumour metastases can affect both bone and liver, in children, and possibly in cirrhosis of the liver. No differences in electrophoretic mobility could be seen between zymograms of different diseases affecting the same organ. Patients presenting with hepatic cirrhosis all showed a marked serum intestinal alkaline phosphatase zone as well as a liver zone on electrophoresis. An intestinal zone was not present with other types of hepatobiliary disease. The heterogeneity of total serum alkaline phosphatase activity in normal subjects is demonstrated, alkaline phosphatases of liver and bone, and sometimes of intestine being present in normal serum. Results obtained in women in the last trimester of pregnancy and in old people are also discussed.